Aplikasi Hara Mikro dan Lengkap Melalui Daun Pada Beberapa Varietas Padi Hibrida China - Herjuna Praba Wisesa; Dwi Harjoko; Ahmad Yunus (Agrosains : Jurnal Penelitian Agronomi, 2018)
Rice is the main product in Indonesia in the context of the supply of rice as a national food. Efforts to increase rice production are faced with various constraints such as fertilization ineffective and under-utilization of hybrid varieties by farmers. This study aims to determine the effect of differences in nutrient application through the leaves on the growth and yield of china’s hybrid rice. The method used is strip plots design. The design consists of two factors, namely the variety and diversity of nutrient factors. There are five varieties of rice that are used with 3 treatments a difference nutrient which is water, micro nutrient, complete nutrient. The results obtained indicate that the applications of micro-complete nutrient through the leaves have outcomes on the growth parameters that affect on plant height and the parameters of production that is the total number of grains per hill, weight of grain content per hill and percentage of grain content. Then, hybrid rice which has the highest potential yield after applying nutrient based on the amount of grain per clump is Hybrid I and Hybrid III.